Responsible corporate governance : towards sustainable and effective governance structures - Aluchna, Maria; Idowu, Samuel O. (Springer, 2017)
This book discusses the tasks and functions of corporate governance in the light of current challenges and the dynamics that arise from a broader approach to company management and the integration of corporate governance with corporate social responsibility (CSR) and sustainability. Addressing the corporate governance shortcomings that are believed to have contributed to the recent financial crisis, it explores the interplay between corporate governance and CSR, and includes examples of company practice to show how such changes affect the practices of shareholders, boards of directors and regulators. In particular, the book examines shareholders' activities, their different investment strategies, specific reporting expectations and the submission of proposals to the annual meeting. Further, for boards of directors it explores the need to revise their tasks with respect to the criteria for executive appointments, their corporate strategy, performance measures and diversity recommendations, while for directors it provides recommendations to reconsider the structure of executive pay and performance incentives. Lastly, for regulators the book investigates the need to introduce new laws addressing, for instance, the need for integrated reporting, limiting the voice of short term oriented shareholders and providing guidelines for executive compensation.
Keywords: Corporate governance.; Social responsibility of business.; Sustainable development.; elektronické knihy; electronic books